MORPHOLOGY OF IN VITRO EXPANDED HUMAN MUSCLE - DERIVED STEM CELLS - Danisovic, Lubos; Varga, Ivan; Polak, Stefan; Ulicna, Marcela; Bohmer, Daniel; Vojtassak, Jan (Biomedical papers, 2008)
BACKGROUND: Skeletal muscle contains populations of multipotent adult stem cells also referred to as muscle-derived stem cells.AIM: The main goal of this study was to isolate and culture human adult stem cells from skeletal muscle and characterize them.METHODS: Muscle-derived stem cells were isolated from biopsy specimens of femoral muscle. The cells were cultured in Dulbecco's modified Eagle's minimal essential medium supplemented with 10% fetal calf serum and gentamycin. When they reached confluence, they were sub-passaged up to the third passage. Cells from the last passage were prepared for TEM analysis. Production of α-actin and desmin was confirmed by histochemistry. Moreover, the phenotypic characterization was performed.RESULTS: Primary isolated muscle-derived stem cells had a fibroblast-like shape. During subsequent passages they maintained this morphology. TEM analysis showed typical ultrastructural morphology of mesenchymal stem cells. They had large pale nuclei with a large amount of euchromatine. Nuclei were irregular with noticeable nucleoli. Dilated cisterns of rough endoplasmic reticulum were present in cytoplasm. In certain parts of the cytoplasm there were aggregates of granules of glycogen. The products of cells were actively secreted into the extracellular matrix. They expressed α-actin and desmin. The results of phenotypic characterization showed that almost all analyzed cells were CD13, CD34, CD56 positive and CD45 negative. Moreover, they did not express anti-human fibroblast surface protein.CONCLUSIONS: Muscle-derived stem cells exhibited typical characteristics typical for mesenchymal stem cells. After analysis of their differentiation potential they could be used in tissue engineering and regenerative medicine.
Keywords: Muscle-derived stem cells/Morphological analysis/Phenotypical analysis